Non-Destructive Model to Predict Commelina diffusa Leaf Area - CARVALHO,L.B. (2017)
ABSTRACT: Leaf length (L), leaf width (W), and leaf area (LA) were measured from 100 leaves aiming to determine a simple linear equation (Y=a*X) to predict the leaf area of Commelina diffusa, an important weed infesting annual and perennial crops in Brazil and worldwide. Results indicate the equation LA=0.7*LW reliably estimates the leaf area of C. diffusa, after correlating LA with LW, and then validating that equation by analyzing four new 25-leaf samples.